Search for supersymmetry in hadronic final states using MT2 in $pp$ collisions at $\sqrt{s} = 7$ TeV - CMS collaboration (2190 authors) (2012)
A search for supersymmetry or other new physics resulting in similar final states is presented using a data sample of 4.73 inverse femtobarns of pp collisions collected at sqrt(s)=7 TeV with the CMS detector at the LHC. Fully hadronic final states are selected based on the variable MT2, an extension of the transverse mass in events with two invisible particles. Two complementary studies are performed. The first targets the region of parameter space with medium to high squark and gluino masses, in which the signal can be separated from the standard model backgrounds by a tight requirement on MT2. The second is optimized to be sensitive to events with a light gluino and heavy squarks. In this case, the MT2 requirement is relaxed, but a higher jet multiplicity and at least one b-tagged jet are required. No significant excess of events over the standard model expectations is observed. Exclusion limits are derived for the parameter space of the constrained minimal supersymmetric extension of the standard model, as well as on a variety of simplified model spectra.